3D FEM Simulation and Experiment Research for Milling Process of Hardened Curved Mold - YUE Cai-xu; HAO Sheng-yu; HUANG Cui; WANG Yan-wu (Journal of Harbin University of Science and Technology)
School of Mechanical and Power Engineering，Harbin University of Science and Technology，Harbin 150080，China) Abstract: In milling process of high hardness curved mold，the change of contact characteristics between cutting tool and workpiece will cause larger fluctuations of cutting force，which will have an adverse effect on tool life and machining quality. Based on key technology of the finite element simulation such as typical friction model， constitutive model and chip separation criterion，the 3D simulation model of surface milling is established by using finite element simulation software Deform-3D. The trajectory of milling cutter was accurately achieved by controlling the relationship of milling cutter position coordinate and time. Based on the experimental results，the variation characteristics of the curved surfaces milling force and the variation rule of milling force under different milling conditions are analyzed. The results show the effectiveness of the simulation.